G. F. Puchta’s Views on the History of State and Law - Golovko, O. M. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article is devoted to problems of German historiosophy of law. It is characterized understanding of history of state and law by German Historical School of Law. Its development was completed by German scientist G. F. Puchta. He was the first who studied customary law and its connection with positive law on modern positions. He focused on the balance between objective and